Incubational Quality of Eggs and Embrional Development of Chickens Depending on the Storage Times - Goncharyk, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The article presents the results of evaluation of the effects of storage periods (1, 5, 8, 11 days) on incubation eggs of chickens of modern specialized egg crosses on their incubation qualities and embryonic development of chickens. The significant influence of the storage period and age of the parent herd on the investigated parameters is established. On the basis of biological control, it was found that the highest number of eggs with a “blood ring“ (6.6 and 8.8%) was observed during the incubation of chicken eggs of “white“ and “brown“ cross, respectively, at the age of 80 weeks for lengthening the storage period until 8 weeks, as well as for eggs, obtained from birds of both crosses for 11-day storage (2.9–5.1%). The largest number of “dysfunctions“ compared to other experimental groups of eggs was found for chicken eggs of the Hayesz brown class at the age of 28 and 60–80 weeks, for the Hayes white cross – at the age of 28–34 and 80 weeks of all storage periods. For the studied crosses, a sharp increase in the yield of weak chicks (up to 1.5–2.2%) was found during the incubation of eggs from poultry 42–60 weeks of age for storage of 8 days and more, as well as 80-week old birds. Thus, qualitative indices of the incubation eggs of chickens of modern specialized crosses are largely determined both by the age of the bird of the parent flock and the duration of the pre-incubation storage of eggs. At acceptable fertility rates of 80-week-old eggs, the level of withdrawability is significantly lower by increasing the number of dead embryos and weak chickens. Extension of the shelf life of incubation eggs leads to an increase in the number of frozen embryos and “dysfunctions“. In order to increase the profitability of the technological process in the incubator, it is necessary to carry out a comprehensive analysis of the expediency of incubating poultry eggs for a different storage period.